HARMONIZING ISLAMIC VALUES WITH TECHNOLOGICAL ADVANCEMENTS FOR SELF-DEVELOPMENT - Ramadhan, Yusfar; Asykur, Asykur; Ali, Ahmad Zulfikar; Mujibno, Mujibno (Reflektika, 2023)
The development of learning innovation in the era of "Industrial Revolution 4.0" will be closely related to educational technology. Both of them can be harmonized into Islamic values. One of them is that learning online or better known as online is something that must be done in the midst of the Covid 19 outbreak. However, many teaching staff are not yet ready, due to the phenomenon of being technologically illiterate or technologically illiterate. Educators who are technologically clueless can reduce the level of professional credibility in front of their students so that students sometimes tend to underestimate them. It can be seen that here lies the harmonization of Islamic values. Considering that students are more familiar with the world of technology and communication because it has become a nutritional intake in gaining knowledge. This phenomenon often occurs around us, including being found at one of the MTs educational institutions. Al-Irsyadiyah, whose address is Dermowebang Village, Sarirejo District, Lamongan Regency, there are several teachers who are said to still be technologically deficient in their learning. So it is still lacking in implementing Islamic values. Therefore, the focus point in this research is how teachers carry out the online learning process, especially for those who are technologically clueless and what impact this has on student learning outcomes and harmonization of Islamic values. With this article, the author hopes that inspiration and solutions will grow for teachers who experience the same problems.Â